Fresno County Bar Association Sponsored Fresno Courthouse Historical Display Case - Watkins, Howard::::::::: (1989)
Hay market at Fresno and K [now Van Ness Ave.] Streets with copper dome on Courthouse; dome later melted and collapsed due to fire